RF 마그네트론 스퍼터링 법으로 제작한 ITZO 박막의 구조 및 광학적 특성 - 김동렬(Dong Ryeol Kim); 배지환(Ji Hwan Bae); 황동현(Dong Hyun Hwang); 손영국(Young Guk Son) (Biuletyn Uniejowski, 2015)
Indium tin zinc oxide (ITZO) thin films were deposited on glass and quartz substrates by RF magnetron sputtering. The substrate temperature varied from $100^{°}C$ to $400^{°}C$. The structural and optical properties of thin films were investigated by X-ray diffraction (XRD), Field Emission Scanning electron microscopy (FESEM) and UV-Visible transmission spectra. It has been found from X-ray diffraction patterns that increasing the substrate temperature, the amorphous structure changes into polycrystalline structure. The FESEM results showed that all ITZO thin films have a smooth surface. The average optical transmittance (400 - 800 nm) was 82% and 80% at all films deposited at $200^{°}C$. The band gap energy ranges 3.41 to 3.57eV and 2.81 to 3.44eV with a maximum value at $200^{°}C$ all substrates temperature.